The dynamical composite Higgs - von Gersdorff, Gero [UNESP]; Ponton, Eduardo; Rosenfeld, Rogerio (Springer, 2015)
We present a simple microscopic realization of a pseudo-Nambu-Goldstone (pNGB) boson Higgs scenario arising from the breaking of SO(5) -> SO(4). The Higgs constituents are explicitly identified as well as the interactions responsible for forming the bound state and breaking the electroweak symmetry. This outcome follows from the presence of four-fermion interactions with a super-critical coupling, and uses the Nambu-Jona-Lasinio mechanism to break the global SO(5) symmetry. The Higgs potential is found to be insensitive to high energy scales due to the existence of an approximate infrared fixed point. The appearance of vector resonances is described and the correspondence with other proposals in the literature established. The model described here is significantly simpler than other recent ultraviolet completions of pNGB scenarios. The observed Higgs mass can be accommodated, and agreement with electroweak precision tests achieved in certain regions of parameter space. There are also new vector-like fermions, some of which may lie within reach of the LHC. In addition, we predict a heavy standard model singlet scalar in the multi-TeV range. The amount of fine-tuning required in the model is studied. Finally, we show that such a scheme can be completed in the ultraviolet by a renormalizable theory.
Keywords: Phenomenological Models; Chiral Lagrangians